Sexual victimization and intellectual disabilities among child welfare involved youth. (May 2021) - Carrellas, Ann; Resko, Stella M.; Day, Angelique G.
Abstract: Background and objective: Youth with intellectual disabilities involved in child welfare systems are at greater risk of sexual victimization than youth who have not been investigated for child maltreatment. This study addresses a gap in the literature regarding older youth with intellectual disabilities who are sexually victimized and pushed to engage in transactional sex while they are transitioning from child welfare systems involvement. It does so by examining risk and protective factors at the individual, micro, exo, and macro systems levels. Participants and setting: This study included 334 youth ages 18–19.5 from a nationally representative sample of 5, 872 child welfare–involved youth. Methods: Multivariate logistic regression models were used to conduct a secondary analysis of the National Survey of Child and Adolescent Well-Being II to examine relationships between intellectual ability, social support, and community environment and sexual victimization and engaging in transactional sex. Results: Results indicate that 2.5 % of the youth experienced sexual victimization in the past 12 months, and 3.9 % had engaged in transactional sex in the past 6 months. The mean intelligence score for these youth was one standard deviation below average ( M = 84.62, SD = 19.60). Being female was associated with experiencing sexual victimization ( Odds Ratio = 17.29, p = .025). Higher intellectual ability scores were associated with lower odds of engaging in paid sexual activity ( Odds Ratio = 0.92, p = .002). Conclusions: This study highlights the need for early identification of intellectual disabilities among child welfare–involved youth, provision of informed social supports and services, and building community connections during transition to prevent sexual victimization.